2015
DOI: 10.1021/acs.est.5b02805
|View full text |Cite
|
Sign up to set email alerts
|

Emissions of Nanoparticles and Gaseous Material from 3D Printer Operation

Abstract: This study evaluated the emissions characteristics of hazardous material during fused deposition modeling type 3D printing. Particulate and gaseous materials were measured before, during, and after 3D printing in an exposure chamber. One ABS and two PLA (PLA1 and PLA2) cartridges were tested three times. For online monitoring, a scanning mobility particle sizer, light scattering instrument, and total volatile organic compound (TVOC) monitor were employed and a polycarbonate filter and various adsorbent tubes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
214
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 178 publications
(237 citation statements)
references
References 12 publications
19
214
4
Order By: Relevance
“…[3337] Our data is consistent with reports that 3-D printing with various ABS filaments releases toluene, ethylbenzene, styrene, and acetophenone and that printing with PLA generates low amounts of toluene. [14,15,17] We note that others have identified caprolactam, lactide, decane, cyclohexanol, methyl methacrylate, n-butanol, and other VOCs during 3-D printing with ABS or PLA filaments [14,17] although these compounds were not observed in our study. There may be several reasons for the observed differences in VOCs identified among studies such as the composition of the polymer filament, printer extrusion temperatures, and sampling methods used by investigators.…”
Section: Resultscontrasting
confidence: 66%
See 1 more Smart Citation
“…[3337] Our data is consistent with reports that 3-D printing with various ABS filaments releases toluene, ethylbenzene, styrene, and acetophenone and that printing with PLA generates low amounts of toluene. [14,15,17] We note that others have identified caprolactam, lactide, decane, cyclohexanol, methyl methacrylate, n-butanol, and other VOCs during 3-D printing with ABS or PLA filaments [14,17] although these compounds were not observed in our study. There may be several reasons for the observed differences in VOCs identified among studies such as the composition of the polymer filament, printer extrusion temperatures, and sampling methods used by investigators.…”
Section: Resultscontrasting
confidence: 66%
“…Kim et al used the same type of real-time TVOC PID monitor as in our study and reported that levels were non-detectable when printing with two different PLA filaments. [15] In our study, some tests with ocean blue, army green and true red PLA yielded TVOC concentrations below the instrument limit of detection. Interestingly, in our study the laser printers that consumed powdered toner had significantly higher TVOC SER u values than the FDM 3-D printer.…”
Section: Resultsmentioning
confidence: 61%
“…Real‐time instruments that measure total particle number concentration from 20 nm to 1 μm (P‐Trak, Model 8525, TSI Inc., Shoreview, MN), size distribution of particles from 5.6 to 560 nm (fast mobility particle sizer [FMPS], Model 3091, TSI Inc.), and size distribution of particles from 0.5 to 20 μm (aerodynamic particle sizer [APS], Model 3321, TSI Inc.) were used to monitor chamber air before, during, and after printing. The P‐Trak and FMPS were used to monitor for the presence of particles smaller than 1 μm which has been the focus for FDM™ printers using base polymer filaments in prior studies . The APS was used to evaluate the release of particles with sizes greater than the upper cutoffs of the P‐Trak and FMPS during printing.…”
Section: Methodsmentioning
confidence: 99%
“…Several filament polymers are available for use in desktop 3‐D printers, including, but not limited to, acrylonitrile butadiene styrene (ABS), polylactic acid (PLA), and polycarbonate (PC). Thermal degradation of polymer filaments during 3‐D printing has been shown to release millions to billions of ultrafine particles (UFP) per minute and numerous organic chemicals into air …”
Section: Introductionmentioning
confidence: 99%
“…The level of harmful emissions can be affected by several factors, such as operational design, printing type, operating temperature, and materials used. Many studies have assessed the FDM method and have identified filament type and temperature as the main factors influencing the generation of harmful agents . When printing at temperatures lower than the manufacturer's recommendations, particle emissions are relatively low or at negligible levels, whereas significant emission rates have been measured at temperatures higher than the manufacturer‐recommended level …”
Section: Introductionmentioning
confidence: 99%